The Composition of the Microbiota in the Full-Term Fetal Gut and Amniotic Fluid: A Bovine Cesarean Section Study - Husso, Aleksi; Lietaer, Leen; Pessa-Morikawa, Tiina; Grönthal, Thomas; Govaere, Jan; Van Soom, Ann; Iivanainen, Antti; Opsomer, Geert; Niku, Mikael (Frontiers in Microbiology, 2021)
The fetal development of the intestinal immune system is stimulated by the maternal microbiota, but it is still unclear whether viable bacteria exist in the healthy fetus. Analysis of such low microbial biomass environments are challenging due to contamination issues. The aims of the current study were to assess the bacterial load and characterize the bacterial composition of the amniotic fluid and meconium of full-term calves, leading to a better knowledge of prenatal bacterial seeding of the fetal intestine. Amniotic fluid and rectal meconium samples were collected during and immediately after elective caesarean section, performed in 25 Belgian Blue cow-calf couples. The samples were analyzed by qPCR, bacterial culture using GAM agar and 16S rRNA gene amplicon sequencing. To minimize the effects of contaminants, we included multiple technical controls and stringently filtered the 16S rRNA gene sequencing data to exclude putative contaminant sequences. The meconium samples contained a significantly higher amount of bacterial DNA than the negative controls and 5 samples contained culturable bacteria. In the amniotic fluid, the amount of bacterial DNA was not significantly different from the negative controls and all samples were culture negative. Bacterial sequences were identified in both sample types and were primarily of phyla Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria, with some individual variation. We conclude that most calves encounter in utero maternal-fetal transmission of bacterial DNA, but the amount of bacterial DNA is low and viable bacteria are rare.